Ethnically correct dolls : toying with the race industry. - Chin, Elizabeth (American Antropological Association, 1999)
The toy industry has touted ethnically correct dolls as a progressive solution to representation and inclusion in the toy box, and in children's lives. Ethnographic work with ten-year-old, poor and working-class black children in New Haven, Connecticut complicates these assertions. These children had very few ethnically correct dolls. Instead, girls had white dolls that they brought into their worlds through styling their hair in ways racially marked as black. Contrasting a case study of Mattel's Shani dolls with an ethnographic look at race and commodities among New Haven kids, this paper locates children's consumption within the context of social inequality, a context examined in few studies of toys or consumption. Taking kids as primary ethnographic subjects suggests ways in which this largely silenced group can speak to larger social and theoretical issues, among them race, class, gender, and age.